MENYELIDIKI TREN UTAMA DALAM DESAIN KEMASAN NEW NORMAL - Wirania Swasty; Nadia Sigi Prameswari (Fakultas Seni Rupa dan Desain ITB, 2022)
The coronavirus disease 2019 (COVID-19) pandemic has changed the people’slifestyles all over the world. This crisis has influenced the packaging design activityas well. Thus, companies should define the new normal packaging that responds to thepandemic situation and new normal living. This study aims to explore the new normalin packaging design by using blog text analysis. Thematic analysis with an inductiveapproach was done using NVivo12 software and an Excel sheet was used to discoverpatterns of common ideas or themes of the new normal packaging design. This studyhas identified 13 key trends in new normal packaging design, including sustainability,e-commerce, and hygienic-centric design. The findings provide insights for packagingdesigners, brand owners, and marketers to create and develop new standard packaging.